Transparency in The Compilation of The Permanent Voter List (DPT) in The Election of The Regent and Vice Regent of Sabu Raijua - TOUSELAK, Agustina Jeniarti; PANDIE, David B.W; SAYRANI, Laurens P. (PT Batara Swastika Harati, 2024)
The General Election is the application of the principle of democracy in a modern country, meaning that the people choose someone to represent them in the context of people's participation in the Implementation of state governance, as well as a series of political activities to accommodate the interests or aspirations of the community. This study aims to determine and analyze transparency in preparing the Permanent Voter List (DPT) in the 2020 Sabu Raijua Regent and Deputy Regent Election. The results of the study show that (1). The Process Indicator shows that the entire process of compiling the DPT is followed by the community, especially the Sabu Raijua Pilkada election (2). The Information Indicator shows the openness of information on the DPT for the 2020 Sabu Raijua Pilkada. It can be seen that all parties, both the community, voters, Bawaslu and candidate pairs, can follow all stages of updating the voter list until the DPT is determined and still guarantee protection for the confidentiality of personal data from voters (3). Media indicators show the use of Sidalih in updating data, conventional media (bulletin boards) in spaces that are easily accessible to the public and the ease for the press to obtain and disseminate information related to the 2020 Sabu Raijua Pilkada DPT (4). The Accessibility Indicator shows that the Sabu Raijua Regency KPU ensures transparency in the Compilation of the 2020 Sabu Raijua Pilkada DPT through the ease of all parties accessing information related to the DPT, using conventional methods (without COVID-19), namely, it can be accessed in public spaces, the Sabu Raijua KPU PPID or electronically through the application or site to protect voting rights.